Pengembangan Inovasi Teknologi Pengolahan Produk Fungsional Makaroni Ikan Gabus (Channa Striata) Di Kelurahan Pangkalan Kerinci Kota Kabupaten Pelalawan - Rahman Karnila; Mirna Liza; Edison Edison; Sumarto Sumarto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
This activity aims to develop technological innovations for processing functional products on snakehead fish macaroni as a new variant of the business during the COVID-19 pandemic in the